Analysis of hydrochar fuel characterization and combustion behavior derived from aquatic biomass via hydrothermal carbonization process - Sawat Poomsawat (Case Studies in Thermal Engineering, 2021)
Using aquatic biomass as a solid fuel is limited by its low energy density, low lignin content and high moisture content. This study investigated upgrading aquatic biomass as a solid fuel using hydrothermal carbonization with temperatures in the moderate temperatures range for a reaction time of 30 min. Thermogravimetric analysis (TGA) tests were used to study the combustion behavior of the raw aquatic biomass and its derived hydrochar during the combustion process. Chemical composition analysis indicated that compared to the raw aquatic biomass, the fuel quality of the derived hydrochar had been improved by increasing the carbon contents with a substantial decrease in the volatile matter and ash content. Furthermore, higher fuel quality of the derived hydrochar was observed with increasing hydrothermal temperature. Similarly, based on the TGA test, the hydrochars had increased ignition temperatures, higher combustion temperatures and higher burnout temperatures compared to the raw aquatic biomass. The combustion characteristic index values for all hydrochar samples derived from water hyacinth and cattail leaves were appropriate for combustion.